THE RELATIONSHIP OF IMPLEMENTING COUNSELING GUIDANCE AND HOME-STUDY FACILITIES TO ACHIEVEMENT MOTIVATION OF STUDENTS' ACHIEVEMENT IN CLASS X STUDENTS OF SMK NEGERI 1 BINTANG BAYU IN ACADEMIC YEAR 2022/2023 - Tumiyem Tumiyem; Yudi Umara; Abdul Rahman (JURNAL EDUSCIENCE, 2023)
This research is an ex-post facto research. The number of samples in this study were class X students of SMK Negeri 1 Bintang Bayu for the 2022/2023 academic year with a total of 120 respondents. Essential testing tests use factual investigations that involve calculating the mean, middle, mode and standard deviation and correlational testing to test the first and second speculations using the second item relationship by comparing rcount with rtable by testing the third speculation using the double connection recipe with two indicators by comparing Fcount and Ftable. The results of the study show that: (1) There is a positive relationship between the implementation of briefing and the achievement inspiration of class X students of SMK Negeri 1 Bintang Bayu with rcount 0.296 > rtable 5% 0.195; (2) There is a positive relationship between learning in the office and achievement inspiration for class X students of SMK Negeri 1 Bintang Bayu, obtained rcount 0.333 > rtable 5% 0.195; (3) There is a joint positive relationship between the implementation of guidance and learning at home on the achievement inspiration of class X students of SMK Negeri 1 Bintang Bayu obtained Fcount 10.855 > Ftable 5% 3.05 with the level of carrying out guidance 4.6% and learning at home 11.08%.Keywords: Guidance and Counseling services, facilities, motivation, achievementAbstrak Penelitian ini merupakan penelitian ex-post facto. Jumlah sampel dalam penelitian ini adalah siswa kelas X SMK Negeri 1 Bintang Bayu tahun ajaran 2022/2023 dengan jumlah keseluruhan sebanyak 120 Â responden. Uji pengujian esensial menggunakan investigasi faktual yang melibatkan untuk menghitung mean, middle, mode dan standar deviasi dan pengujian korelasional untuk menguji spekulasi pertama dan kedua menggunakan hubungan butir kedua dengan membandingkan rhitung dengan rtabel dengan menguji spekulasi ketiga menggunakan resep koneksi dua kali lipat dengan dua indikator dengan membandingkan Fhitung dan Ftabel. Hasil kajian menunjukkan bahwa: (1) Terdapat hubungan positif antara pelaksanaan pengarahan dengan inspirasi pencapaian siswa kelas X SMK Negeri 1 Bintang Bayu dengan rhitung 0,296 > rtabel 5% 0,195; (2) Ada hubungan positif antara pembelajaran di kantor dengan inspirasi berprestasi siswa kelas X SMK Negeri 1 Bintang Bayu, diperoleh rhitung 0,333 > rtabel 5% 0,195; (3) Terdapat hubungan positif secara bersama antara pelaksanaan bimbingan bimbingan dan pembelajaran di rumah terhadap inspirasi pencapaian siswa kelas X SMK Negeri 1 Bintang Bayu diperoleh Fhitung 10,855 > Ftabel 5% 3,05 dengan tingkat melaksanakan bimbingan 4,6% dan pembelajaran di rumah 11,08%.Kata Kunci: Layanan Bimbingan dan Konseling, fasilitas, motivasi, prestasi